Fiscal Deficit, Current Account Deficit, and Capital Flows in India : An Empirical Investigation Using Granger Causality Test - Kubendran, N. (Arthshastra Indian Journal of Economics & Research, 2018)
The relationship between fiscal deficit and current account deficit has always been a debatable topic among the academicians in the field of economics and finance. In this context, the present study focuses on fiscal deficit, current account deficit, capital flows, and its sub components called debt and non-debt creating capital flows for analysis. The main aim of the study was to analyze the impact of fiscal deficit on current account deficit, capital flows, and its subcomponents. The present study employed the descriptive statistical techniques, Augmented Dickey-Fuller test, and Granger causality test. The empirical findings clearly proved the appropriateness of the twin deficit model for India. The Granger causality test found unidirectional causality between fiscal deficit and current account deficit. Also, the study found unidirectional causality between current account deficit and capital flows. Both the results implied that there was an influence of fiscal deficit on current account deficit, which in turn influenced capital inflows. The study observed bidirectional causality between current account deficit and non-debt creating capital flows, and no causality was observed between current account deficit and non-debt creating capital flows. It can be inferred that there was a direct relationship between fiscal deficit and current account deficit, which in turn influenced debt - creating capital influences into India. Therefore, this paper suggested that the Government of India should be careful in implementing expansionary fiscal policy. Also, the study suggested that the Government of India needs to focus more on fiscal discipline for economic stability and external sector sustainability.